Aeration and Shear Stress Are Critical Process Parameters for the Production of Oncolytic Measles Virus - Grein, Tanja A.; Loewe, Daniel; Dieken, Hauke; Weidner, Tobias; Salzig, Denise; Czermak, Peter (Frontiers in Bioengineering and Biotechnology, 2019)
Oncolytic Measles virus is a promising candidate for cancer treatment, but clinical studies have shown that extremely high doses (up to 1011 TCID50 per dose) are required to effect a cure. Very high titers of the virus must therefore be achieved during production to ensure an adequate supply. We have previously shown that Measles virus can be produced in Vero cells growing on a Cytodex 1 microcarrier in serum-containing medium using a stirred-tank reactor (STR). However, process optimization and further process transfer or scale up requires the identification of critical process parameters, particularly because the use of STRs increases the risk of cell damage and lower product yields due to shear stress. Using a small-scale STR (0.5 L working volume) we found that Measles virus titers are sensitive to agitator-dependent shear, with shear stress ≥0.25 N m 2 reducing the titer by more than four orders of magnitude. This effect was observed in both serum-containing and serum-free medium. At this scale, virus of titers up to 1010 TCID50 mL 1 could be achieved with an average shear stress of 0.1 N m 2. We also found that the aeration method affected the virus titer. Aeration was necessary to ensure a sufficient oxygen supply to the Vero cells, and CO2 was also needed to regulate the pH of the sodium bicarbonate buffer system. Continuous gassing with air and CO2 reduced the virus titer by four orders of magnitude compared to head-space aeration. The manufacture of oncolytic Measles virus in a STR can therefore be defined as a shear-sensitive process, but high titers can nevertheless be achieved by keeping shear stress levels below 0.25 N m 2 and by avoiding extensive gassing of the medium.